2015
DOI: 10.1038/srep15316
|View full text |Cite
|
Sign up to set email alerts
|

Computational evidence that fast translation speed can increase the probability of cotranslational protein folding

Abstract: Translation speed can affect the cotranslational folding of nascent peptide. Experimental observations have indicated that slowing down translation rates of codons can increase the probability of protein cotranslational folding. Recently, a kinetic modeling indicates that fast translation can also increase the probability of cotranslational protein folding by avoiding misfolded intermediates. We show that the villin headpiece subdomain HP35 is an ideal model to demonstrate this phenomenon. We studied cotransla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
0
10
0
1
Order By: Relevance
“…Kinetic modeling predicted that increasing the polypeptide elongation speed can promote cotranslational folding by reducing the number of misfolding events during the time that the ribosome dwells in the misfoldingprone nascent-chain length regime, contrary to the common view that slow synthesis favors native structure formation (31). Consistent with this hypothesis, recent experiments (32,33) and the qualitative trends observed in atomistic molecular dynamics simulations of a small protein (28) imply that slow-translating codons are not always beneficial for cotranslational folding and can promote protein aggregation.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Kinetic modeling predicted that increasing the polypeptide elongation speed can promote cotranslational folding by reducing the number of misfolding events during the time that the ribosome dwells in the misfoldingprone nascent-chain length regime, contrary to the common view that slow synthesis favors native structure formation (31). Consistent with this hypothesis, recent experiments (32,33) and the qualitative trends observed in atomistic molecular dynamics simulations of a small protein (28) imply that slow-translating codons are not always beneficial for cotranslational folding and can promote protein aggregation.…”
Section: Introductionmentioning
confidence: 77%
“…The relationship between elongation rates and cotranslational events is beginning to be quantitatively understood through theoretical, computational and experimental efforts (16,20,(25)(26)(27)(28)(29)(30). Kinetic modeling predicted that increasing the polypeptide elongation speed can promote cotranslational folding by reducing the number of misfolding events during the time that the ribosome dwells in the misfoldingprone nascent-chain length regime, contrary to the common view that slow synthesis favors native structure formation (31).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence of computational analysis that fast translation speed can increase the probability of cotranslational protein folding. [75][76][77] It is now important to consider the coding sequence while performing protein folding in silico. In this regard, the recently developed CSandS database is worth to consider while designing protein three-dimensional structure.…”
Section: Translation Kinetics Guides Cotranslational Protein Foldingmentioning
confidence: 99%
“…A cellular model should also include non-equilibrium processes, for their importance in regulating protein stability (Samiotakis et al 2009;Gershenson and Gierasch 2011;Wang et al 2015;Bui and Hoang 2016;Gorensek-Benitez et al 2017). Toward this goal, recent simulations of cotranslational folding showed that translation rates may affect the structure and stability of misfolding-prone proteins (Trovato and O'Brien 2017), as well as of multidomain proteins (Tanaka et al 2015).…”
Section: Toward Realistic Molecular Simulations Of Cellular Eventsmentioning
confidence: 99%